High-resolution aeromagnetic survey of Calabria (Southern Italy). Issue 2 (30th November 2017) - Vecchio, Antonio; Minelli, Liliana; D'Ajello Caracciolo, Francesca; Nicolosi, Iacopo; Bottari, Carla; Carluccio, Roberto; Celi, Rossella; Chiappini, Stefano; Giuntini, Alessandra; Materni, Valerio; Messina, Alfio; Mochales, Tania; et al.
ABSTRACT: We present a 1:350, 000 high-resolution magnetic anomaly map of Calabria (Southern Italy), obtained by merging the results from two low-altitude aeromagnetic surveys performed in southern and northern Calabria. Magnetic anomalies of Calabria are of low intensity, and mostly range from 11 to –9 nT. Northern Calabria is characterized by positive anomalies in the Tyrrhenian margin (Coastal Chain) that turn into negative values moving eastward in the Sila Massif. Southern Calabria is characterized by slightly positive anomaly values, interrupted by a null magnetic anomaly corridor roughly corresponding to the eastern margin of the Gioia Tauro basin. Finally, anomaly values turn systematically negative in the Messina Straits. Due to the unprecedented resolution (low flying height, spatial sampling along the flight line of ∼5 m and 1–2 km flight line spacing), the new map highlights, in detail, the geometry and setting of the upper crustal features. As Calabria is one of the most seismically active regions in Italy, hit by several high-magnitude earthquakes in recent centuries, the interpretation of this new map will hopefully contribute to new insights into the crustal geological setting, location and dimension of the main seismogenic sources.